Alcohol excise taxes as a percentage of retail alcohol prices in 26 OECD countries. (1st February 2021) - Ngo, Anh P.; Wang, Xuening; Slater, Sandy; Chriqui, Jamie F.; Chaloupka, Frank J.; Yang, Lin; Smith, Lee; Li, Qing; Shang, Ce
Highlights: Measures of excise taxes as a percentage of alcohol prices have not been systematically studied. Trend of excise taxes as a percentage of retail alcohol prices during 2003–2018 was evaluated for 26 OECD countries. Tax burden on alcoholic beverages is low in OECD countries. In most countries, excise taxes as a percentage of prices did not change over time. There is ample room for increasing excise taxes, particularly for beer and wine. Abstract: Background: Many countries have implemented alcohol excise taxes. However, measures of excise taxes as a percentage of alcohol prices have not been systematically studied. Methods: Data on the retail prices of alcoholic beverages sold in stores and excise taxes in 26 countries during 2003–2018 was from the Economist Intelligence Unit price city data and the Organization for Economic Co-operation and Development (OECD) tax database. The percentages of excise taxes in off-premise retail prices were derived as the ratio of taxes to prices at different price levels. Changes of excise taxes over time were assessed using negative binominal regressions. Results: The percentage of excise taxes in average off-premise alcohol prices was from 5 % in Luxembourg to 59 % in Iceland for beer, and from 0 % in France to 26 % in Iceland for wine. Excise taxes accounted for 5% of discount liquor prices in Czech Republic to 41 % in Sweden for Cognac, for 19 % in the United States (US) to 67 % in Sweden for Gin, for 13 % in the US to 63 % in Australia for Scotch Whisky six years old, and for 6 % in Iceland to 76 % in Sweden for Liqueur Cointreau. There were no significant changes in the percentage of excise taxes in alcohol prices over time in most countries except for Nordic countries. While wine had the lowest excise taxes, liquors had the highest tax burden. Conclusion: Tax burden on alcoholic beverages is low in OECD countries, indicating ample room for increasing alcohol excise taxes, particularly for beer and wine in those countries.